mRNA-seq analysis of the Gossypium arboreum transcriptome reveals tissue selective signaling in response to water stress during seedling stage. - Xueyan Zhang (Public Library of Science (PLoS), 2013)
The cotton diploid species, Gossypium arboreum, shows important properties of stress tolerance and good genetic stability. In this study, through mRNA-seq, we de novo assembled the unigenes of multiple samples with 3h H(2)O, NaCl, or PEG treatments in leaf, stem and root tissues and successfully obtained 123,579 transcripts of G. arboreum, 89,128 of which were with hits through BLAST against known cotton ESTs and draft genome of G. raimondii. About 36,961 transcripts (including 1,958 possible transcription factor members) were identified with differential expression under water stresses. Principal component analysis of differential expression levels in multiple samples suggested tissue selective signalling responding to water stresses. Venn diagram analysis showed the specificity and intersection of transcripts' response to NaCl and PEG treatments in different tissues. Self-organized mapping and hierarchical cluster analysis of the data also revealed strong tissue selectivity of transcripts under salt and osmotic stresses. In addition, the enriched gene ontology (GO) terms for the selected tissue groups were differed, including some unique enriched GO terms such as photosynthesis and tetrapyrrole binding only in leaf tissues, while the stem-specific genes showed unique GO terms related to plant-type cell wall biogenesis, and root-specific genes showed unique GO terms such as monooxygenase activity. Furthermore, there were multiple hormone cross-talks in response to osmotic and salt stress. In summary, our multidimensional mRNA sequencing revealed tissue selective signalling and hormone crosstalk in response to salt and osmotic stresses in G. arboreum. To our knowledge, this is the first such report of spatial resolution of transcriptome analysis in G. arboreum. Our study will potentially advance understanding of possible transcriptional networks associated with water stress in cotton and other crop species.